The Effect of Isometric Exercises and lidocaine 2% on Pain Relief during Intravenous Propofol Injection: A Randomized Clinical Trial - Mahdieh Anjidani; Abbasali Mehrabadi; Arezoo Davarinia Motlagh Quchan; Mostafa Khaleghipour; Sedighe Rastaghi; Ali Asghar Jesmi; Zohreh Mohamadzadeh Tabrizi (Mashhad University of Medical Sciences, 2022)
injection.Aim: This study was performed aimed to compare the effect of isometric exercises and lidocaine 2% on pain relief during intravenous propofol injection.Method: This randomized clinical trial (RCT) study was performed in 2020 on 106 patients who were candidates for general anesthesia for different surgical treatments in Neyshabur 22 Bahman Hospital. The subjects were randomly allocated into three groups by permuted block randomization. Group A received propofol 1% with 40 mg lidocaine 2%, group B received pure propofol 1%, and group C completed 5 cycles of isometric exercises before injection of 1% pure propofol. Data collection tools consisted of a demographic information questionnaire and Ambesh four-point scale. Data were analyzed by SPSS software (version 16) and Fisher's exact test, Mann-Whitney U test, and analysis of variance (ANOVA). P<0.05 was considered statistically significant.Results: The majority of patients underwent general surgery. There was no significant difference between pain intensity in groups A and C, but group B reported significantly higher pain intensity than the intervention groups (P<0.001).Implications for Practice: The use of both lidocaine 2% and isometric exercises reduces the pain intensity of propofol injection. Therefore, the use of these two methods is recommended.